Simulação em Python da operação do economizador de uma caldeira piloto de leito fluidizado circulante - Kagesawa, Gustavo Naoki Shibatta (2022)
Circulating fluidized bed (CFB) boilers are widely applied for electric power generation, due to the wide variety of fuel that can be used and the excellent combustion efficiency. The economizers are heat exchangers used in those type of boilers to preheat of the water fed into the liquid-steam separator tube. This device allows the heat exchange between exhaust gases and the water, up to the last one achieve an appropriate value below the saturation temperature on the operational pressure. In this thesis, a concentric tube economizer is studied with the aid of programming in Python language. Mathematical modeling was performed for six specific conditions operating conditions of an economizer coupled to a lab-scale circulating fluidized bed boiler steam generator, in order to determine the effect produced on the mass flow of preheated water and the exhaust gas outlet temperature. The simulation results showed that exhaust gas inlet temperature was the parameter with the greatest influence on its outlet temperature, always being above 150 ºC to avoid condensation of water vapor. On the other hand, the pressure of the liquid fed to the economizer was the variable that promoted the greatest changes in the mass flow of the water, which could be useful for further control of equipment installed on a laboratory scale.